2008
DOI: 10.1021/ja802027u
|View full text |Cite
|
Sign up to set email alerts
|

Inspection of the Duality of a Verdazyl-Based Radical in Transition Metal Complexes: A π* Donor Ligand and a Magnetic Partner

Abstract: The behavior of a verdazyl-based radical bound to open-shell transition metal ions in the structurally and magnetically characterized [M(hfac)2imvd(o)] (M = Mn, Ni; hfac = (1,1,1,5,5,5)hexafluoroacetylacetonate; imvd(o) = 3-(2'-imidazolyl)-1,5-dimethyl-6-oxoverdazyl) complexes is rationalized using ab initio wave-function-based calculations analysis. The calculated exchange coupling constants J (H = -J(s(M) x s(imvd(o)); J(Mn)(calcd) = -63 cm(-1), J(Ni)(calcd) = 205 cm(-1)) are in excellent agreement with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 44 publications
1
69
0
Order By: Relevance
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 90%
See 1 more Smart Citation
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 90%
“…So far, the DDCI approach has been extensively employed in the evaluation of J in molecular and solid state magnetic materials with a remarkable good agreement with experiment. [20][21][22][23][24][25][26][27][28][29][30][31][32] Some years ago we took benefit of this methodology to analyze in depth the physical contributions to the magnetic coupling on a series of binuclear Cu ͑II͒ complexes. 33 The use of the DDCI strategy allows not only to obtain quite accurate J values but also to analyze the various physical effects by generating CI spaces of increasing lengths that include different types of determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Among the abundant class of multicentric architectures involving open-shell metal ions, paramagnetic ligand-based systems have turned out to be promising targets to enhance the exchange interactions. 8,13,14 The originality of such systems stems from the intrinsically molecular character of the magnetic orbitals, in contrast with standard paramagnetic metal ion-based systems. In this respect, thiazyl or verdazyl radical ͑vdz͒ containing ligands represent interesting targets toward strongly coupled discrete [15][16][17][18] and extended [16][17][18][19] molecule-based magnetic systems.…”
Section: Introductionmentioning
confidence: 99%
“…As prime examples, the magnetic behaviors of ͓Ni͑imvdz͒͑hfac͒ 2 ͔ and ͓Mn͑imvdz͒͑hfac͒ 2 ͔ complexes have been recently elucidated. 14 Since the ferromagnetism of ͑1͒ is weak, conclusions drawn from a naive crystal field picture might thus be misleading. Wave function-based calculations were performed to clarify the origin of the magnetic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these two criteria provides a very powerful scheme and illustrative applications of the method can be found in the Refs. [81][82][83].…”
Section: Other Applications Of Ddcimentioning
confidence: 99%